The usufruct in ongoing codification of Civil Law in Serbia - Popov, Danica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Usufruct is the right of using and taking the fruits of something belonging to another. It was understood to be given for the life of the receiver the usufructuary, unless of shorter period was expressed, and then it was to be restored to the owner in the good condition as when it was given except for ordinary wear and tear In this paper, the author points some legal solutions pertaining to the institute of usufruct as envisaged in the Draft Civil Code, and in the Draft Code on Property and  other  Rights. This institute in the Republic of Serbia positive Law has not been comprehensively regulated yet, but in the most of cases we still apply the legal provisions contained in the Serbian Civil Code of 1884. For the first time in modern legal  history  in Serbia, usufruct is completely  regulated in the Draft Civil Code, in about 42 articles and in the 43 articles in the Draft Code on Property and another Rights. In addition, the author s focus is on the object of usufruct. Providing that both Drafts will be adopted, the Serbian legislation will obtain a modern institute of usufruct.